STUDI FILOGENETIK ELANG LAUT PERUT PUTIH (Haliaeetus leucogaster) BERDASARKAN DNA BARCODING CYTOCHROME-C OXCIDACE SUB UNIT I (COI) - Riri Wiyanti Retnaningtyas; Windri Hermadhiyanti; Dwi Listyorini (Universitas Sebelas Maret, 2014)
The White-bellied Sea Eagle (Haliaeetus leucogaster) is one of the top predators living in the coastal area of Indonesia. This species has the range of distribution in all across Indonesian archipelago. However, this raptor population decreases particularly in the Java southern seas due to illegal hunts and the decreasing quality of their natural habitat. Meanwhile, this bird is still poorly studied in Indonesia. This research focuses on the identification of Haliaeetus leucogaster and the phylogenetic study of this species by means of morphometrical analysis and DNA barcode cytochrome-c oxcidace sub unit I (COI) in regards to the conservation of thisspecies. The method used in this research is by measuring the morphological characteristics and mitochondrial DNA isolation using Forward primer BirdF1 5’- TTC TCC AAC CAC AAA GAC ATT GGC AC-3’ and Reverse primer BirdR2 5’ ACT ACA TGT GAG ATG ATT CCG AAT-3’. The phylogenetic analysis using MEGA 6 with Maximum Likelihood method shows that Haliaeetus leucogaster in this study is closely related to Haliaeetus albicilla, Haliaeetus leucocephalus dan Haliaeetus pelagicus. Keywords: phylogenetic study, Heliaeetus leucogaster, morphological chacarteristics, DNA barcoding, Cytochrome-c Oxcidace Sub Unit I (COI)